Predisposing Factors for Methadone Poisoning in Children Hospitalized at Kerman Afzalipour Hospital, Iran - Hosseininasab, Ali (Addict Health, 2016)
BACKGROUND: Methadone is a synthetic opioid that has been used to relieve severe pain in addiction withdrawal. Unfortunately, due to non-standard supply and storage, the incidence of poisoning and deaths caused by this drug is increasing daily. The purpose of this study was to determine the underlying causes of methadone poisoning in children admitted to Kerman Afzalipour Hospital, Kerman University of Medical Sciences, Iran, during 2012. METHODS: This cross-sectional study was performed on 105 children diagnosed with methadone poisoning and admitted to the pediatric emergency ward at Kerman Afzalipour Hospital. The required information was recorded through interviews with parents, patient examination, and if necessary telephone calls with the parents. The data were analyzed using SPSS software. FINDINGS: Mean age of children was 3.9 ± 2.4 years and 59.0% of them were boys. Most parents had a high school diploma or a lower level of education. In all cases, a family member or relative, or at least one person in a party they attended was an addict. In most cases, methadone was fed to the child by mistake instead of water or other drugs. Parental substance abuse, employment status, and family income were significantly associated with methadone poisoning. CONCLUSION: Training of methadone storage in individuals who need to use this drug can help to prevent accidental ingestion and poisoning of children.